In This Issue - David Briggs (ACHSM, 2020)
Welcome to this fourth issue of the year, a record in the number of issues produced and yes, we continue to receive significant numbers of articles for publication. We appreciate the enthusiasm of authors but ask for their patience in our ability to process, peer review and publish. Exciting news for the APJHM was that we have been accepted for inclusion in the Directory of Open Access Journals (DOAJ). Allowing that organisation to speak for itself, we quote 'We are absolutely delighted to welcome this journal into DOAJ and look forward to seeing the article metadata soon.' The benefits of supplying DOAJ with our metadata are said to be:    - Statistics show more than 900 000-page views and 300 000 unique visitors a month to DOAJ from all over the world.    - Many aggregators, databases, libraries, publishers, and search portals collect DOAJ free metadata and include it in  their products. Examples are Scopus, Serial Solutions and EBSCO.    - DOAJ is OAI compliant and once an article is in DOAJ, it is automatically harvestable.    - DOAJ is Open URL compliant and once an article is in DOAJ, it is automatically linkable.    - Over 95% of the DOAJ Publisher community said that DOAJ is important for increasing their journal's visibility    - DOAJ is often cited as a source of quality, open access journals in research and scholarly publishing circles.' This is encouraging news for our authors, readers the ACHSM and SHAPE who are involved and supportive of the APJHM. The first article in this issue is an important commentary from the National President of ACHSM, Dr Neale Fong, who provides insights into leadership and management in the Covid_19 period, the positioning of the College and its offerings at this time and an announcement about the commencement of a certification process for College members. The editorial again addresses the continuing progress of Covid-19 internationally. The editorial focusses on lessons learned across a number of nation states with a hope that this will encourage health professionals, policy makers, politicians, communities to reflect on the experience so far and develop a reasonably consistent framework and strategy that might improve future approaches to pandemic management. We would welcome contributions in this context. Turato and Oprescu describe enablers for allied health front-line managers in public health environments to deliver sustainable patient care in a review article in the Australian context. This article is followed by Yousef Yaghoobi and colleagues designing an empowerment model for Iranian health centre managers: A comprehensive study that examine empowerment models for Iranian health centre managers to develop capabilities and competencies for this group. Muddle in a research article describes the relationship between leadership style and hospital employee engagement in Papua New Guinea. Arya provides a distinctly unique contribution in being a fine detective in learning health leadership lessons to conclude this group of articles particularly relevant to health management. The next group of articles commences with the contribution of Bain, Goswami, Lloyd and Davis describing the post-implementation evaluation of a digital dictation system in a large health service using HOT-Fit framework, in Victoria Australia. This is followed by an article by seven colleagues from Iran that provides a research article on the assessment of staff performance in a CSSD unit using a 360-degree evaluation method. A further group of colleagues from Iran have also provided systematic review and meta-analysis of the care burden of informal care givers of haemodialysis patients, concluding that we should develop appropriate strategies to improve the quality of life for this group.The next contribution from Yadav from India provides a comparative study of health as an economic dimension in respect to China and India. Colleagues from Nepal, Thailand and Australia make a topical contribution entitled 'infodemic monikers in social media during the covid-19 pandemic. Das and colleagues provide a contribution that addresses community preparedness and responses to prevention and control of Covid_19 in Bangladesh. As usual we conclude with our library bulletin provided by Yaping Liu.